Urbanization and Winter Precipitation: A Case Study Analysis of Land Surface Sensitivity - Bradford D. Johnson; Marcus D. Williams; J. Marshall Shepherd (Atmosphere, 2021)
Urban modification of precipitation regimes is well documented in the urban climate literature. Studies investigating urbanization and non-convective precipitation, specifically winter precipitation, are limited. The theoretical framework here argues that the collective influence of urbanization extends beyond traditional city limits and the surrounding rural areas and can impact regional climate in non-adjacent cities. This paper utilizes the weather research and forecasting model (WRF-ARW) to simulate a cold-season synoptic system over the Northeastern United States over a variety of urban land surface scenarios. This case study centers on the potential boundary layer urban heat island effect on the lower troposphere and its ability to impact winter precipitation type at the local to regional scales. Results show a significant reduction in temperatures near the modified surface and subtle reductions over adjacent urban areas. When surface wind speeds are less than 5 ms−1, the boundary layer heat island increases air temperatures on the order of 3–4 °C at altitudes up to 925 mb. When combined with encroaching warm air near 850 mb during transitional precipitation events, the boundary layer heat island increases the thickness of the melting layer and consequently exposes falling hydrometeors to longer melting duration and phase change. Model simulations also show regional connections through remote temperature and relative humidity changes in urban areas removed from reforested areas.